Readings in library and information science Dr.S P Sood festschrift - Sood, S P; Pawan, Usha (Ed.); Vyas, S D (Ed.) (Jaipur Raj Publishing House, 2000)
The volume contains 33 articles written by 40 professionals grouped into 9 sections (i)Library Science Education(ii)Ranganathan and Library Science(iii)Colon Classification(iv)Library Legislation(v)Library budget,etc.etc.
Keywords: Library science; Library education; Information science; Library legislation; Information technology; Academic libraries